Differential distribution patterns and assembly processes of soil microbial communities under contrasting vegetation types at distinctive altitudes in the Changbai Mountain - Kang, Yujuan; Wu, Haitao; Zhang, Yifan; Wu, Qiong; Guan, Qiang; Lu, Kangle; Lin, Yiling (Frontiers in Microbiology, 2023)
Diversity pattern and community assembly process of soil microorganism is essential for comprehending soil biodiversity and ecosystem processes. Although soil microorganisms play key roles in the stability and succession of forest ecosystems, their responses to altitude gradient and soil depth have not been investigated at spatial scale. Using 16S and ITS rRNA gene sequencing this study determined the responses of diversities and assembly processes of bacterial and fungal communities to altitude and soil depth in mountain ecosystems. Our results revealed soil bacterial diversity showed a U-shaped altitude pattern at 0-10 cm depth and reached a minimum at 1800 m, while fungal diversity monotonically decreasing with altitude increased. At 10-20 cm soil depth, bacterial diversity exhibited no apparent altitudinal gradient, while fungal Chao1 and PD indices showed hump-shaped patterns with altitude increased and reached a maximum at 1200 m. Although soil bacterial and fungal communities were distinctively distributed with altitude, their turnover rates insignificantly differed between soil depths. Soil physiochemical variables and climate factors significantly correlated with the β diversity of bacterial and fungal community at two soil depths, suggesting both soil variables and climate heterogeneity contributed to the variation of bacterial and fungal community. Correspondingly, a novel phylogenetic null model analysis demonstrated that the community assembly of soil bacterial and fungal communities were respectively dominated by deterministic and stochastic processes, and greatly affected by altitude and soil depth. The processes of the bacterial community were significantly related to soil DOC and C:N ratio, while the assembly processes of fungal community were significantly related to the soil pH and C:N ratio. Our results provide a new perspective to assess responses of soil microbial communities to variations with altitude and soil depth.